2020
DOI: 10.1007/s00018-020-03647-z
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of membrane-protein and protein–protein interactions control membrane remodeling by epsin 1 and affects clathrin-mediated endocytosis

Abstract: Membrane remodeling is a critical process for many membrane trafficking events, including clathrin-mediated endocytosis. Several molecular mechanisms for protein-induced membrane curvature have been described in some detail. Contrary, the effect that the physico-chemical properties of the membrane have on these processes is far less well understood. Here, we show that the membrane binding and curvature-inducing ENTH domain of epsin1 is regulated by phosphatidylserine (PS). ENTH binds to membranes in a PI(4,5)P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Previous studies reported the use of Dyn K44A [ 34 , 50 , 72 ] and Pitstop2 [ 51 , 73 , 74 ] as means by which to investigate the clathrin-mediated pathway. In addition to the significant changes in BILF1 internalization induced by the inhibitors, we also observed an increase in receptor expression after the addition of Dyn K44A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the use of Dyn K44A [ 34 , 50 , 72 ] and Pitstop2 [ 51 , 73 , 74 ] as means by which to investigate the clathrin-mediated pathway. In addition to the significant changes in BILF1 internalization induced by the inhibitors, we also observed an increase in receptor expression after the addition of Dyn K44A.…”
Section: Discussionmentioning
confidence: 99%
“…Given that epsins themselves are able to induce membrane curvature 50 , 51 , it was possible that impaired CCS invagination resulted from compromised localization of epsins in the presence of CK-666. To test this possibility, we applied CK-666 or DMSO to Ptk2 cells ectopically expressing mCherry-CLC and EGFP-epsin1 and imaged cells by TIRF microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, lowers the energy barrier to induce membrane curvature (Steinem and Meinecke 2020). The mechanism of decreasing lateral membrane tension and generation of curvature depends on AH insertion and the lipid-specific oligomerization of the ENTH domain (Kroppen et al 2020). It therefore seems reasonable to assume that ENTH-dependent membrane remodeling relies on different molecular mechanisms that combine cooperativity of protein-lipid and protein-protein interactions.…”
Section: Epsin1mentioning
confidence: 99%